Interpretasi Hukum Pasal 15 Ayat (2) Huruf g Undang-Undang Jabatan Notaris - Yudhana Hendra Pramapta (Faculty of Law Universitas Islam Indonesia, 2022)
The existence of the authority of a Notary in making the minutes of the auction deed in Article 15 paragraph (2) letter g of Notary Position Law (UUJN) has its own legal consequences. This is due to the discovery of vague norms in Article 15 paragraph (2) letter g UUJN, and conflicts between legal norms (antinomy norms) between Article 15 paragraph (2) letter g UUJN and Consitutional Court Regulation (PMK) No. 189/PMK.06/2017 on Class II Auction Officers. In addition, there is debate about the nature of the minutes of the auction deed that must be in accordance with Article 38 UUJN or Article 37 Vendu Reglement. The researcher formulates two problems, first, what is the legal interpretation regarding the authority of a Notary in making a deed of minutes of auction deed in UUJN? Second, what is the nature of the minutes of auction deed made by a Notary as Class II Auction Officer? The research method used is normative juridical with literature study. The results of the study concluded that PMK No. 189/PMK.06/2017 can be waived due to the principle of Lex Superior Derogat Legi Inferiori and a Notary who wishes to hold concurrent positions as Class II Auction Officer can be directly appointed by the Ministry of Finance without having to go through stages such as selection and work practice (apprenticeship). In addition, the deed of minutes of auction as an authentic deed (Ambtelijke Acte) drawn up by a Notary must comply with the provisions of Article 37 Vendu Reglement based on the principle of Lex Specialis Derogat Legi Generalis.Key Word: Legal Interpretation, Minutes of the Auction Deed AbstrakAdanya kewenangan Notaris dalam membuat akta risalah lelang dalam Pasal 15 ayat (2) huruf g UUJN memberikan akibat hukum tersendiri. Hal tersebut dikarenakan ditemukannya norma yang kabur (vage normen) dalam Pasal 15 ayat (2) huruf g UUJN, dan konflik antar norma hukum (antinomy normen) antara Pasal 15 ayat (2) huruf g UUJN dengan PMK No. 189/PMK.06/2017 tentang Pejabat Lelang Kelas II. Selain itu, adanya perdebatan mengenai sifat akta risalah lelang tersebut harus sesuai dengan Pasal 38 UUJN atau Pasal 37 Vendu Reglement. Peneliti merumuskan dua rumusan masalah, pertama, bagaimana interpretasi hukum mengenai kewenangan Notaris dalam membuat akta risalah lelang dalam UUJN? Kedua, bagaimana sifat akta risalah lelang yang dibuat oleh seorang Notaris selaku Pejabat Lelang Kelas II? Metode penelitian yang digunakan adalah yuridis normatif dengan studi kepustakaan. Hasil penelitian menyimpulkan bahwa PMK No. 189/PMK.06/2017 dapat dikesampingkan karena adanya asas Lex Superior Derogat Legi Inferiori dan seorang Notaris yang hendak merangkap jabatan sebagai Pejabat Lelang Kelas II dapat langsung diangkat oleh Kementerian Keuangan tanpa harus melalui tahapan seperti seleksi dan praktik kerja (magang). Selain itu, akta risalah lelang sebagai akta otentik (Ambtelijke Acte) yang dibuat oleh Notaris harus mengikuti ketentuan Pasal 37 Vendu Reglement berdasarkan asas Lex Specialis Derogat Legi Generalis.Kata-kata Kunci: Interpretasi Hukum, Akta, Risalah Lelang